2018
DOI: 10.1007/s11235-018-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

End-user traffic policing for QoS assurance in polyservice RINA networks

Abstract: Looking at the ever-increasing amount of heterogeneous distributed applications supported on current data transport networks, it seems evident that best-effort packet delivery falls short to supply their actual needs. Multiple approaches to Quality of Service (QoS) differentiation have been proposed over the years, but their usage has always been hindered by the rigidness of the TCP/IP-based Internet model, which does not even allow for applications to express their QoS needs to the underlying network. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The C/U matrix has an MxN matrix where M represents the delay, and N represents the loss [13]. This matrix-based approach has been studied in [14], and the authors demonstrated that incorporating ∆Qbased scheduling policy enhanced network performance with heterogeneous distributed applications.…”
Section: Related Workmentioning
confidence: 99%
“…The C/U matrix has an MxN matrix where M represents the delay, and N represents the loss [13]. This matrix-based approach has been studied in [14], and the authors demonstrated that incorporating ∆Qbased scheduling policy enhanced network performance with heterogeneous distributed applications.…”
Section: Related Workmentioning
confidence: 99%
“…The experiment established 6 IP VPNs, with 4 CE routers at each IP VPN. The core DIF uses Quantitative Transport Agreement (QTA) resource allocation policies [16] to support four classes of service (QoS cubes) with differential loss In this experiment we analyzed how the complete naming and addressing architecture embodied by RINA allows RINA networks to be renumbered live, without significantly impacting the performance perceived by existing flows or impairing the ability to crate new ones. Renumbering a network with multiple layers today is a maintenance event: it has to be carefully planned, requires humans in the loop, and it takes one or more days to complete.…”
Section: Providing Qos Guaranteesmentioning
confidence: 99%
“…The experiment established 6 IP VPNs, with 4 CE routers at each IP VPN. The core DIF uses Quantitative Transport Agreement (QTA) resource allocation policies [16] to support four classes of service (QoS cubes) with differential loss and delay: urgent, low loss and urgent, high loss and non-urgent, low loss and best effort. Figure 9 shows the Cumulative Distribution Functions (CDF) of the end-to-end delay experienced by flows between PE routers, for medium-and high-load scenarios in two configurations: one in which the DIF uses FIFO (First In First Out) schedulers, and the other QTA schedulers.…”
Section: Providing Qos Guaranteesmentioning
confidence: 99%